POTENTIAL DEVELOPMENT OF BAU NYALE TRADITION AS CULTURAL TOURISM IN LOMBOK - Taufiq Ramdani; Nuning Juniarsih; Ratih Rahmawati (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
The development of tourism potential is not only in nature tourism but culture tourism, the community protects cultural tourism in Lombok by carrying out the routine customs of Bau Nyale (re: Bau is catching, Nyale is sea worms). Traditional customs traditions are carried out as an effort to preserve culture in the form of entertainment and ritual processions. This is done as a dynamic in the recovery of the economic sector while developing the potential for cultural tourism in the Mandalika SEZ. This research is qualitative research with an exploratory approach, the phenomenon is analyzed with the theory of Symbolic Interactionism by George Herbert Mead, with a component of community social action in developing the potential of cultural tourism in Lombok. The result of the research is the Bau Nyale tradition with the adaptation of new habits carried out with wisdom to be an innovation in introducing the Sasak tradition to the wider community. Although in its implementation there is a reduction in activities, the potential of tradition is still manifested in a series of ceremonial events, so that it still exists as an attraction for the surrounding community and tourists, in addition, the historical site of the Princess Mandalika Statue is a priority area to visit. The involvement of human resources is important in the process of developing cultural tourism as an implementer of cultural socialization and promotion, implementers of cultural values and norms, with the synergy of local governments and traditional figures who contribute to the implementation.